Alterations in the gut microbiota of alcoholic cirrhosis patients infected with Clonorchis sinensis in the Pearl River Delta region of China - Aijun Huang; Minxuan Su; Shebin Zhang; Chanjing Zhao; Yanfen Luo; Yifei Long; Dongling Lin; Song Li; Cong Shen; Qiwei Li; Yimei Cai; Lina Wang; et al. (PLoS ONE, 2025)
Clonorchiasis, a foodborne parasitic disease caused by Clonorchis sinensis ( C. sinensis ), is prevalent in certain regions of Asia and can result in severe hepatobiliary complications, including cholangiocarcinoma, peribiliary fibrosis, and hepatic fibrosis. In certain regions of China, the concurrent consumption of raw freshwater fish and alcohol, which are components of the local dietary culture, has contributed to the high prevalence of this disease. Infected individuals often endure the dual burden of clonorchiasis and alcoholic liver disease (ALD). While both C. sinensis infection and alcohol abuse can disrupt the gut microbiota, the synergistic mechanisms of these two factors in patients with alcoholic cirrhosis (ALC) remain poorly understood. This study aims to elucidate the impact of C. sinensis infection on the gut microbiota of patients with ALC, with the objective of identifying potential diagnostic or therapeutic targets. A total of 64 patients diagnosed with ALC were recruited for this study, with half of the participants infected with C. sinensis and the other half remaining uninfected. Fresh fecal samples were collected from all participants. Alterations in the gut microbiota were analyzed using high-throughput sequencing of the 16S ribosomal RNA gene derived from the fecal samples. Our results showed that analysis of β-diversity revealed significant differences in gut microbial communities between C. sinensis -infected and non-infected groups ( P < 0.05). The Linear discriminant analysis effect size (LEfSe) identified the phylum Firmicutes (highest LDA score at the phylum level) and the genus Prevotella (dominant at the genus level) as key taxa driving gut microbial composition differences in patients with ALC and C. sinensis infection ( P < 0.05). Correlation analysis at the genus level demonstrated significant negative associations between Enterococcus and multiple bacterial genera in the C. sinensis -infected group. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis further highlighted divergent metabolic pathways between groups, with the vancomycin resistance pathway showing the most pronounced disparity. In conclusion, patients with ALC and C. sinensis infection show alterations in gut microbiota compared to non-infected counterparts. Notably, specific bacteria such as Prevotella and Enterococcus may represent potential targets for the development of novel diagnostic and therapeutic strategies for ALC patients afflicted by C. sinensis infection.